First recovery in anorexia nervosa patients in the long-term course: a discrete-time survival analysis - Herzog, Wolfgang; Schellberg, Dieter; Deter, Hans-Christian (Journal of consulting and clinical psychology, 1997)
The results of a 12-year follow-up study of occurrence and timing of first recovery in 69 hospitalized patients with severe anorexia nervosa (AN) are presented. For the first time discrete-time survival analysis methods were used to determine the likelihood of recovery in AN patients. Furthermore, predictors gleaned from pretreatment-posttreatment studies of long-term outcome in AN could be evaluated as to their effect on a change in the time course structure of the likelihood of first recovery. Results show that AN condition did not improve until after 6 years after the first inpatient treatment in 50% of patients. However, a restricter-type AN and low serum creatinine levels were predictors for earlier recovery. One specific effect was that AN patients who show purging behavior in combination with additional social disturbances have a lower chance of recovering. The use of discrete-time survival analysis methodology in further prospective studies will contribute to the development of more tailored treatment of AN, which also takes the individual phase of illness and specific aspects of the symptomatology into account. (PsycInfo Database Record (c) 2025 APA, all rights reserved)